ARCHITECTURE IN THE ISLAMIC CIVILIZATION: MUSLIM BUILDING OR ISLAMIC ARCHITECTURE - Yassin, Ayat Ali; Utaberta, Dr. Nangkula (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2012)
The main problem of the theory in the arena of islamic architecture is affected by some of its Westernthoughts, and stereotyping the islamic architecture according to Western thoughts; this leads to the breakdownof the foundations in the islamic architecture. It is a myth that islamic architecture is subjected to theinfluence from foreign architectures. This paper will highlight the dialectical concept of islamic architecture ormuslim buildings and the areas of recognition in islamic architecture. It will also widen the knowledge in thecharacteristics of each point in time according to the stages of islamic architecture from the prophetic agemoving through the architecture outside the city of Medina, the Caliphs, the Umayyad, Abbasid, andarchitectural models by spatial and time periods, taking Iraq as the example to explain how the Islam influentson architecture and vice versa.